(untitled) (Journal of the Bangladesh Agricultural University, 2014)
The study was conducted to evaluate the effect of antibiotic on shelf life in rohu fish, Labeo rohita (Hamilton) under ice storage condition. Oxytetracycline (OTC), the most widely used antibiotic, was fed to rohu (average body weight 16.0 g) at the rate of 2 g/kg through fish diet for 5 days and their shelf life was determined in iced condition. Organoleptically, fish were found to be acceptable up to 16 days before becoming inedible compared to 15 days for control fish which received pelleted diet with no antibiotic under the same condition. Initial moisture, ash, protein, lipid, NPN and TVB-N values were 70.42±1.91%, 2.80±0.10%, 17.90±0.50%, 3.12±0.04%, 0.0086±0.01% and 17.43±0.60 mg/100g respectively in the control which reached at values of 78.45±1.50%, 3.84±0.10%, 13.47±1.00%, 2.80±0.08%, 0.0053±0.001%, 26.17±0.76 mg/100g, respectively after 16 days of ice storage. There was no significant difference for these values compared to control group. In case of total bacterial load, values of aerobic plate count (APC) was 2.0±0.1×103 during the start of ice storage condition which increased significantly to 5.6±0.38×107, exceeding the acceptable limit for ice stored fish. The APC values also did not show any significant variation compared to control fish, suggesting that the use of antibiotic in fish diet had little or no effect on shelf life of rohu fish during ice storage condition. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19946 J. Bangladesh Agril. Univ. 11(2): 385-390, 2013